Mapping human sensory responses in 2D and 3D environment / Anitawati Mohd Lokman and Assoc. Prof. Dr. Nor Laila Md Noor - Mohd Lokman, Anitawati; Md Noor, Nor Laila (Assoc. Prof. Dr.) (2006)
Despite the rapid growth in online sales of clothing, some consumers are still reluctant to purchase clothing over the Internet. This is due to disability of online consumer to actually seeing and handling products the way they do in physical environment, and therefore influence their choices, expectation and eventually satisfaction with the product. When selecting a garment, it is a consumer's instinct to use the haptic or sense of touch, other than visual judgment, to describe and assess the fabric quality and its suitability for a specific end use. The sense of touch to fabric is referred to as 'fabric hand'. Currently, several research projects are addressing the problem of fabric drape simulation. Some commercial systems are already on-line where the drape of a garment can be visualized. While consumer can have similar visual sensory judgment, purchasing garment over the internet still has no sense of the 'hand' of the fabric, or fabric hand. The purpose of this study is to map consumers' sensory perception and preference in 2D and 3D environment. 5 different fabric types are assessed and compared in order to interpret the relationship between visual and tactile sensory responses. The result shows that, even though there are differences in fabric hand judgment between physical and virtual environment, overall sensory perception and fabric preference are same. The outcome of the study is hoped to give initial idea of how much consumers are able to judge the sense of touch visually and tactilely in physical and virtual environment.